Thoracic Computed Tomography to Assess ARDS and COVID-19 Lungs - Barbas, Carmen Silvia Valente (Frontiers in Physiology, 2022)
This paper discusses the role of Thoracic Computed Tomography in the diagnosis of Acute Respiratory Distress Syndrome (ARDS) and COVID-19 lungs. The ARDS lungs compared to normal lungs are characterized by non-aerated lungs in the lowermost lung regions, the compressive atelectasis, and progressively more aerated lung tissues from the lower to upper lungs levels characterizing the ARDS heterogenous lungs with its vertical gradient, areas of possible high shear stress and ventilator-induced lung injury during positive pressure ventilation. Besides helping to the correct diagnosis of ARDS, Thoracic Computed tomography adds in adjustments of PEEP, tidal volume, and prone position during mechanical ventilation and follow-up of the ARDS patients during their hospital stay as well as in the detections of possible intra-thoracic complications. Now, at COVID-19, thoracic tomography is the most sensitive imaging technique for the diagnosis showing diffuse lung involvement, mainly in lungs periphery, ranging from ground-glass opacities to parenchymal consolidations revealing that compromised lung volume loss increased the risk for oxygenation support and the risk for intubation. Pulmonary dual-energy angio-tomography in COVID-19 patients showed a significant number of pulmonary ischemic areas even in the absence of visible pulmonary arterial thrombosis which may reflect micro thrombosis associated with COVID-19 pneumonia. A greater thoracic tomography severity score is independently related to poor outcomes.